MATERIALS INSERTION OF LOCAL PLANTS IN LEARNING OF BIOLOGY IN CLASS X TO IMPROVE ATTITUDE TO PRESERVE BIODIVERSITY - Ardan, Andam S. (Jurnal Pendidikan Matematika dan IPA, 2022)
Biodiversity in the form of plants is a nation's wealth that needs to be maintained and developed by the government and the people of Indonesia. However, to keep it, the community must be introduced to the wealth of plants around it so that it fosters an attitude of caring, belonging, and nurturing. Meanwhile, the government makes rules so that the richness of plant biodiversity is not destroyed, destroyed, or transferred to other countries. One effective way to introduce the richness of plant biodiversity is through formal education, in this case, lessons at school. Schools are expected to convey the message of the importance of plant biodiversity, its types, and how to maintain it in learning materials. All notes can be inserted at any level of education, from kindergarten, elementary, junior high, high school to university. For materials in high school, some biology materials can be used to foster an attitude of maintaining biodiversity, one of which is plants' material world. For this reason, it is necessary to include plant material in learning so that students' love for plants becomes stronger around them, ultimately resulting in an attitude of caring for biodiversity.